A super lightweight UHPC–HSS deck panel for movable bridges. (15th April 2016) - Ghasemi, Sahar; Zohrevand, Pedram; Mirmiran, Amir; Xiao, Yulin; Mackie, Kevin
Highlights: Proposed a lightweight waffle deck as a combination of two high-strength materials. Applicable to movable bridges, bridge deck replacement, and bridge widening. Experiments showed capacity and ductility of the proposed deck system. Demonstrating an effective panel action, center rib takes only 1/3 of the live load. Punching of thin slab should not be a design concern. Abstract: Movable bridges often include open grid steel deck for its light weight and ease of installation. These decks, however, suffer from poor rideability and high maintenance costs. In search for a new generation of lightweight solid decks that address these issues, a novel system was recently developed using ultra-high performance concrete (UHPC) in the form of a low-profile asymmetric waffle slab reinforced with high-strength steel (HSS) rebars. The deck was shown as a structurally viable alternative, yet its overall weight including haunches and connections exceeded the weight limits for deck replacement on some existing movable bridges. The purpose of this study was to optimize the design of proposed UHPC–HSS deck system to meet the weight limits for existing movable bridges. The size and reinforcement of the proposed deck were modified in two phases, and five specimens with single or multiple ribs were tested in simple or two-span configurations. Test results have shown that the optimized section with an overall depth of 102 mm and the main longitudinal reinforcement of No. 16 M (16 mm) can suitably meet the load demand, ductility and serviceability requirements, while staying within the weight limits of 1.0 kN/m 2 for a movable bridge with a stringer spacing of 1.2 m.